دلالة التداخل الزمني في القرآن الكريم - فنير, حنان صالح عبدالله (Sharwes Scientific Journal, 2024)
language has its temporal structures that clarify its meaning in rhetorical molds that attract attention and contemplation. Each morphological formula has temporal connotations originally set for it, which grammarians have determined in the three verbs: past, present, and imperative. However, these formulas may indicate other times than the original ones in different contexts. This is the concept of: temporal overlap in the Holy Quran (the subject of the research). From here, the research problem focuses on the main question: What are the rhetorical and interpretive connotations of temporal overlap in the Holy Quran? The research aims to identify the rhetorical connotations in the use of overlapping tenses in the Holy Quran and their effects on understanding the texts. The method used is descriptive and analytical inductive, by inducting some verses in which temporal overlap is clear, describing it and analyzing it semantically. The research reached the most important results, which are: temporal overlap is part of the linguistic and rhetorical miracle of the Quran